Economic, Social and Cultural Rights in the Transitional Justice Remit - Pokhrel, Shreejana (Kathmandu School of Law Review, 2013)
This paper begins by explaining why confronting the past is essential for securing lasting peace, justice and sustainable reconciliation in the society through appropriate and comprehensive transitional justice approaches. Then the paper argues about the notion of the indivisibility of economic and social rights (hereinafter ESCR) in terms of injustices which may have been both a root and a product of conflict, including the possible remedies for violations. The paper also deals with the international legal framework and practices towards the justiciablity of ESCR in relation to TJ and illustrates two country specific case examples where the TJ initiatives have embraced economic disparity, social injustices and discrimination in an attempt to audit the past for forward-looking strategies. This is followed by concluding remarks to reinforce arguments of the entire essence of the paper.